Dynamic light scattering and transmission electron microscopy in drug delivery: a roadmap for correct characterization of nanoparticles and interpretation of results - Filippov Sergey K.; Khusnutdinov Ramil; Murmiliuk Anastasiia; Inam Wali; Zakharova Lucia Ya.; Zhang Hongbo; Khutoryanskiy Vitaliy V. (ROYAL SOC CHEMISTRY, 2025)
In this focus article, we provide a scrutinizing analysis of transmission electron microscopy (TEM) and dynamic light scattering (DLS) as the two common methods to study the sizes of nanoparticles with focus on the application in pharmaceutics and drug delivery. Control over the size and shape of nanoparticles is one of the key factors for many biomedical systems. Particle size will substantially affect their permeation through biological membranes. For example, an enhanced permeation and retention effect requires a very narrow range of sizes of nanoparticles (50-200 nm) and even a minor deviation from these values will substantially affect the delivery of drug nanocarriers to the tumour. However, amazingly a great number of research papers in pharmaceutics and drug delivery report a striking difference in nanoparticle size measured by the two most popular experimental techniques (TEM and DLS). In some cases, this difference was reported to be 200-300%, raising the question of which size measurement result is more trustworthy. In this focus article, we primarily focus on the physical aspects that are responsible for the routinely observed mismatch between TEM and DLS results. Some of these factors such as concentration and angle dependencies are commonly underestimated and misinterpreted. We convincingly show that correctly used experimental procedures and a thorough analysis of results generated using both methods can eliminate the DLS and TEM data mismatch completely or will make the results much closer to each other. Also, we provide a clear roadmap for drug delivery and pharmaceutical researchers to conduct reliable DLS measurements.